Pengaruh Teknologi Finansial (Fintech) Terhadap Partisipasi Mahasiswa UIN Jurai Siwo dalam Investasi Syariah - Kharis Arwana; Arya Nanda Perdana; Lukman Hakim; Esty Apridasari (Indonesia Economic Journal, 2025)
This study aims to analyze the influence of financial technology (fintech) on the participation of IAIN Metro students in sharia investment. The rapid growth of fintech in Indonesia, especially sharia-based fintech, has not been fully in line with the increase in literacy and investment participation among the younger generation. This study uses a quantitative approach with a survey method of 30 students who have used the sharia investment fintech application. Data were collected through questionnaires and analyzed using multiple linear regression. The results of the study indicate that fintech has a significant and positive effect on student participation in sharia investment, both partially and simultaneously. The regression model built has met the classical assumptions including normality, linearity, and the absence of multicollinearity. These findings confirm that ease of access, conformity to sharia principles, and user-friendly digital features of fintech services are important factors that encourage student involvement in Islamic value-based investment. This study provides an empirical contribution to the sharia fintech literature as well as practical implications for digital platform developers and educational institutions in increasing sharia financial inclusion among the younger generation.